Reproductive Biology of Two Freshwater Small Indigenous Fishes Securicula gora and Gudusia chapra of Narmada River, Madhya Pradesh - Sayoo, Baiakhuidlang M; Minare, Anubhuti; Vyas, Vipin; Siddiqui, Shadab (Asian Journal of Biological and Life Sciences)
Investigation of reproductive biology is an important aspect for knowing the reproductive behaviour of any species. In the present study, the reproductive biology of Securicula gora and Gudusia chapra was study for six months from August 2023 to 15 January 2024 in the Department of Zoology and Applied Aquaculture, Barkatullah University, Bhopal. The main aim of this study was to determine the reproductive cycle through observation of gonado somatic index, fecundity, ovary weight, Maturity stages, and spawning season of Securicula gora and Gudusia chapra, which were collected from Narmada River from Dongawada site Narmadapuram District. The length and weight of both fishes were measured. GSI was calculated by the standard method, Fecundity was calculated by sub-sampling method and ova diameter was measured with the help of ocular-micrometre. About 120 individuals were dissected and the result revealed that the average GSI value for S. gora and G. chapra peak at similar times in October month there is 14.86±2.78 and 5.7±2.15, respectively. The maximum average for fecundity recorded in September month for S. gora was 7664.44±6255.5 and 10900.07±598.59 in month of September for G. chapra. Similarly, the maximum ovary weight recorded for S. gora was 1.28±0.58 g in the month of September and for G. chapra 1.13±59 g in the month of October respectively. The study provides the basic information of the reproductive pattern of both fish species which will be helpful for the management of the fish stock to promote conservation of such fishery resources.
Keywords: Reproductive Biology; Gonadosomatic index; Fecundity; Ovary weight; Maturity stages; Spawning Period